2023
DOI: 10.9734/air/2023/v24i3938
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of English Speaking Skills in the Relationship between Social Literacy and the Engagement of Students

Abstract: This study determined the mediating role of English speaking skills in the relationship between social literacy and student engagement in colleges and universities in Davao Oriental, Philippines. A non-experimental quantitative research design using descriptive-correlational research design was applied and employed stratified random sampling with 313 Education college students as a sample. Data collection was made through a survey instrument. Data analysis was done through Mean, Pearson-r, Multiple Regression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This means that that the level of English speaking skills among English major students in Region XI is oftentimes practiced. These significant results relate to the findings of the study ofRulona and Bacasmot (2023) which found that the level of SL in terms of intellectual skills, social skills, cooperation skills, and social attitude and values among students in Davao Oriental is high which means that SL is oftentimes observed on many occasions. Further, Quin (2017) also found that social and behavioral engagement has an impact on student participation since both enable possibilities for developing relationships, setting of clear limits and opportunities, and opportunity of collaborating with others and with personal interaction.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…This means that that the level of English speaking skills among English major students in Region XI is oftentimes practiced. These significant results relate to the findings of the study ofRulona and Bacasmot (2023) which found that the level of SL in terms of intellectual skills, social skills, cooperation skills, and social attitude and values among students in Davao Oriental is high which means that SL is oftentimes observed on many occasions. Further, Quin (2017) also found that social and behavioral engagement has an impact on student participation since both enable possibilities for developing relationships, setting of clear limits and opportunities, and opportunity of collaborating with others and with personal interaction.…”
supporting
confidence: 72%
“…Aside from that, despite the many studies conducted showing the bivariate relationships between SE and SL (Ngoyi et al, 2014) and SE and ESS (Binnendyk, 2020), previous researchers have not come across of studying the same variables and research design used in the present study which was published in the Philippines. On the other hand, there is a published and existing study about the effect of ESS on the relationship between SE and SL (Rulona & Bacasmot, 2023), but it was conducted using a quantitative research design in descriptive-correlational approach. Hence, it is now the present study which will add new body of knowledge using these variables in different approach.…”
Section: Introductionmentioning
confidence: 99%
“…Language acquisition, particularly of an internationally recognized language such as English, is increasingly viewed as a means of achieving academic and professional success (Rulona & Bacasmot, 2023). This importance grows in the field of childhood education since it effects cognitive development, communication skills, and future academic trajectories.…”
Section: Introductionmentioning
confidence: 99%